2020
DOI: 10.1111/os.12757
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Sectional Area Measurement Techniques of Soft Tissue: A Literature Review

Abstract: Evaluation of the biomechanical properties of soft tissues by measuring the stress–strain relationships has been the focus of numerous investigations. The accuracy of stress depends, in part, upon the determination of the cross‐sectional area (CSA). However, the complex geometry and pliability of soft tissues, especially ligaments and tendons, make it difficult to obtain accurate CSA, and the development of CSA measurement methods of soft tissues continues. Early attempts to determine the CSA of soft tissues i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 108 publications
(171 reference statements)
0
11
0
Order By: Relevance
“…Of course, there are many means to measure tissue thickness [24,10]. However, none we found fulfilled our need for i) being non-destructive, ii) having a high spa-tial resolution, iii) providing continuous spatial maps, and iv) being fast.…”
Section: Introductionmentioning
confidence: 88%
“…Of course, there are many means to measure tissue thickness [24,10]. However, none we found fulfilled our need for i) being non-destructive, ii) having a high spa-tial resolution, iii) providing continuous spatial maps, and iv) being fast.…”
Section: Introductionmentioning
confidence: 88%
“…The chicken tendons were acquired from the third digit, which was the longest and therefore considered more suitable for study [ 12 , 13 ]. The cross section area (CSA) was calculated by approximating the cross section to an ellipse [ 14 , 15 ] ( S = Πab/4, where a and b are the average values of major and minor axes of the ellipse measured three times by a vernier-caliper with a precision of 0.02 mm, which was placed vertically to the long axis of the tendon). The CSA of tendons of porcine (23.544 ± 4.450 mm 2 ) and chicken (2.076 ± 0.511mm 2 ) is significantly different, representing two different sizes of tendons to simulate the different sizes encountered in the clinic [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…The length of the tendons was measured, followed by the determination of the cross-sectional area (CSA). Several methods have been proposed dealing with the determination of the CSA, such as [29][30][31][32]. Therefore, as fast specimen preparation has to be fulfilled to reduce tissue dehydration as much as possible, the method presented in [29] was chosen to be applied in this study since it is reported as simple, rapid, and non-destructive method.…”
Section: Specimen Preparationmentioning
confidence: 99%